Myoclonus status revealing COVID 19 infection. (January 2023) - Ben Mohamed, Dina; Zouari, Rania; Ketata, Jihen; Nabli, Fatma; Blel, Samir; Ben Sassi, Samia
Abstract: Introduction: At the beginning of the coronavirus virus (COVID-19) pandemic, the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV2) was thought to cause mainly respiratory symptoms, largely sparing the brain and the rest of the nervous system. However, as the knowledge about COVID-19 infection progresses and the number of COVID19-related neurological manifestations reports increases, neurotropism and neuroinvasion were finally recognized as major features of the SARS-CoV-2. Neurological manifestations involving the central nervous system are sparse, ranging from headaches, drowsiness, and neurovascular attacks to seizures and encephalitis [1] . Thus far, s everal cases of non-epileptic myoclonus were reported in critical patients [2, 3 ]. Here, we report the first case of myoclonus status as the inaugural and sole symptom of COVID-19 in a conscious patient. Observation: A 60-year-old man with unknown family history and no medical issues other than smoking one cigarette packet a day over the span of 25 years. The patient presented with 5 days of abnormal movements in bilateral arms following the COVID vaccination. They were described as brief, involuntary jerking, like in sleep starts, in the proximal part of their upper members, and his face with a regular tremor in his arms exacerbated by movements and emotion. His movement disorder worsened the second day, and he developed an abnormal gait with slurred speech, concomitantly with diarrhea. Seven days following the symptoms onset, the patient was alert. His neurological exam revealed multifocal myoclonic jerks affecting four limbs predominantly proximal, the face, and the trunk (video 1). The myoclonic jerks were sensitive to tactile and auditory stimuli, without enhanced startle response or hyperekplexia. His gait was unsteady due to severe myoclonus, without cerebellar ataxia (video 2) and he had mild dysarthria. No dysmetria at the finger-to-nose and heel-to-shin tests were found. Examination of eye movements revealed paralysis of Down-Gaze and no opsoclonus was detected. Physical exam was unremarkable, including lack of fever and meningitis signs. The electroencephalogram (EEG) did not show any abnormalities concomitant with myoclonic jerks (Fig. 1 ). The cerebral Magnetic Resonance Imaging (MRI) was normal (Fig. 2). An extensive biological work-up including a complete blood count, a comprehensive metabolic panel, an arterial blood gas analysis, a urine drug screen, a thyroid function test, a vitamin B12, folate, and ammonia level, and HIV and syphilis serologies were inconclusive. Testing for autoimmune and paraneoplastic antineuronal antibodies including anti-NMDA-R was negative. The cerebrospinal fluid (CSF) study was unremarkable (0.3 g/l of proteinorachia, 1 white blood cell). Polymerase chain reaction (PCR) for herpes simplex virus, varicella-zoster virus, and SARS-CoV-2 in CSF was negative. However, the patient tested positive for COVID-19 through PCR for viral RNA from the nasopharyngeal swab. After the administration of 12mg/day of Dexamethasone for 3 days, along with clonazepam and levetiracetam, the patient's symptoms started improving on day 3 and he displayed a very slow but progressive recovery. Discussion: Our patient presented with acute isolated multifocal myoclonus status without cognitive impairment. These movements were prominent, spontaneous, worsened by action, and sensitive to touch and sound. The anatomical source of this myoclonus could be cortical or subcortical despite the absence of evident EEG discharges. Several diseases can cause acute myoclonus such as severe hypoxia, metabolic disturbances, and paraneoplastic syndromes. these diagnoses were ruled out in our patient. Post-vaccinal origin was also suggested, but its accountability was not proven. Thus, the two hypothetic etiologies raised were either para-infectious or infectious mechanisms in relation to SARS-Cov 2 infection. HIV, VZV, HSV, and syphilis infections were eliminated and the patient tested positive for SARS-Cov2 infection. In the literature, COVID-19-related myoclonus was reported as a complication of an already-known SARS-CoV-2 infection in about 50 patients so far. It generally occurs between 6 days and 26 days following the SARS-CoV-2 infection [2–5], and affects critical illness patients with cognitive decline, mainly from the intensive care unit [3, 4 ]. Yet, our patient did not display any symptoms of COVID-19 infection before the occurrence of these abnormal movements. Furthermore, he had a relatively good general condition and no cognitive impairment. Several pathophysiological mechanisms were suggested regarding the COVID-19-related myoclonus. Either central nervous invasion by SARS-Cov 2 after transneuronal spread and/or auto-immune cross-reactivity reaction, are likely incriminated in the pathophysiology of most of the cases [6] . We believe that there is an inflammatory process involved with increased levels of proinflammatory cytokines and systemic inflammation, including cytokine storm or cytokine release syndrome targeting the brain and more specifically the cortex and basal ganglia [6] . Data collection in clinical registries is needed to increase our knowledge of the prevalence of neurological symptoms in patients with COVID-19 and will hopefully clarify the causal relationship between SARS-CoV-2 infection and post-COVID-19 myoclonic syndrome.